UMMUNA HAJJAH SITTI RAIHANUN ZAINUDDIN ABDUL MADJID: ULAMA PEREMPUAN DAN TRANSFORMASI PENDIDIKAN ISLAM DI LOMBOK-NUSA TENGGARA BARAT - Ulyan Nasri; Abdul Malik Salim Rahmatullah (An-Nahdlah: Jurnal Pendidikan Islam, 2023)
This research aims to explore the role and contributions of Sitti Raihanun in the transformation of Islamic education in West Nusa Tenggara. The method employed is a literature review, collecting data through the exploration of relevant literature. Data analysis techniques involve organizing information related to Sitti Raihanun's life journey, thoughts, and contributions in developing Islamic educational institutions in the region. The findings provide a profound insight into how Sitti Raihanun played a key role in reshaping Islamic education in West Nusa Tenggara. The implications of these findings include a better understanding of her influence in enhancing the quality of Islamic education and empowering the local community. This research significantly contributes to the literature on the history of Islamic education and the role of female scholars in Indonesia. It is hoped that the results of this study will inspire further efforts to improve education and empower communities through approaches inspired by Sitti Raihanun.